2015
DOI: 10.1177/1745691615594577
|View full text |Cite
|
Sign up to set email alerts
|

Decentering and Related Constructs

Abstract: The capacity to shift experiential perspective—from within one’s subjective experience onto that experience—is fundamental to being human. Scholars have long theorized that this metacognitive capacity—which we refer to as decentering—may play an important role in mental health. To help illuminate this mental phenomenon and its links to mental health, we critically examine decentering-related constructs and their respective literatures (e.g., self-distanced perspective, cognitive distancing, cognitive defusion)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
257
1
21

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 414 publications
(313 citation statements)
references
References 118 publications
(271 reference statements)
11
257
1
21
Order By: Relevance
“…Broadly, MDD is associated with a loss of biological and behavioral flexibility (Kashdan & Rottenberg, 2010; Stange, Alloy, & Fresco, in press). Specifically, MDD is characterized by inflexible physiological responses (Bylsma, Salomon, Taylor-Clift, Morris, & Rottenberg, 2014), difficulty disengaging from perseverative thinking processes such as rumination, and with mentally distancing oneself from one’s negative thinking (Nolen-Hoeksema, Wisco, & Lyubomirsky, 2008; Fresco et al, 2007a; Bernstein et al, 2015). Furthermore, healthy individuals who are inflexible in response to changes in environmental or emotional context also may be susceptible to developing depression (Stange et al, in press).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Broadly, MDD is associated with a loss of biological and behavioral flexibility (Kashdan & Rottenberg, 2010; Stange, Alloy, & Fresco, in press). Specifically, MDD is characterized by inflexible physiological responses (Bylsma, Salomon, Taylor-Clift, Morris, & Rottenberg, 2014), difficulty disengaging from perseverative thinking processes such as rumination, and with mentally distancing oneself from one’s negative thinking (Nolen-Hoeksema, Wisco, & Lyubomirsky, 2008; Fresco et al, 2007a; Bernstein et al, 2015). Furthermore, healthy individuals who are inflexible in response to changes in environmental or emotional context also may be susceptible to developing depression (Stange et al, in press).…”
mentioning
confidence: 99%
“…Decentering refers to a set of characteristics involving three related metacognitive processes (Bernstein et al, 2015): meta-awareness, an awareness of one’s subjective experience in consciousness, such as feeling and thinking (e.g., “I am having the thought that I am stupid” rather than “I am stupid”); disidentification from internal experience, the experience of internal states as being separate from one’s self (e.g., “I am having a feeling of sadness” rather than “I am sad”); and reduced effects of thought content on other mental processes, such as attention and emotion. Interestingly, decentering is inversely associated with PC (Fresco et al, 2007a; Kaiser, Andrews-Hanna, Metcalf, & Dimidjian, 2015), and experimental studies have demonstrated that low decentering mediates the relationship between rumination and negative thinking in depression (Lo et al, 2014).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Approaching feelings this way diminishes the power a feeling can have over the 26 individual, and enables one to live life without being a victim of one's own thoughts (Anālayo 2006, p. 222). Related to this, psychological studies have shown that the ability to decenter from one's thoughts, feelings, etc., is linked to better mental health and wellbeing (Bernstein et al 2015). Such mindful observations also gradually cultivate a person's ability to withstand varied experiences.…”
Section: Theoretical Foundations For Mindfulness Practicesmentioning
confidence: 99%